2017
DOI: 10.3389/fmed.2017.00230
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Physical Frailty and Associated Physical and Functional Impairments in Mild Cognitive Impairment

Abstract: ObjectiveTo characterize the physical frailty phenotype and its associated physical and functional impairments in mild cognitive impairment (MCI).MethodParticipants with MCI (N = 119), normal low cognition (NLC, N = 138), and normal high cognition (NHC, N = 1,681) in the Singapore Longitudinal Ageing Studies (SLAS-2) were compared on the prevalence of physical frailty, low lean body mass, weakness, slow gait, exhaustion and low physical activity, and POMA balance and gait impairment and fall risk.ResultsThere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 52 publications
(54 reference statements)
2
24
0
Order By: Relevance
“…Gender, age, cognition level, and existing comorbidities are significant predictors or confounders of physical function and hospital outcomes so ideally all studies would adjust for these variables . Gender and age were frequently reported among the eligible studies.…”
Section: Resultsmentioning
confidence: 99%
“…Gender, age, cognition level, and existing comorbidities are significant predictors or confounders of physical function and hospital outcomes so ideally all studies would adjust for these variables . Gender and age were frequently reported among the eligible studies.…”
Section: Resultsmentioning
confidence: 99%
“…Fourth, the slight association of sociodemographic variables with the two dimensions suggested that this approach of frailty showed very little association with sociodemographic aspects not corroborating previous studies (Bieniek et al, 2016;Nyunt et al, 2017;Papachristou et al, 2017;Lewis et al, 2018), which should be the subject of further research, considering these two dimensions of the frailty phenotype and across different age groups. This study analyzed only the oldest old people with very low variability in education level and health condition, as referred to in the Limitations section.…”
Section: Discussionmentioning
confidence: 67%
“…Regarding the frailty phenotype, participants were considered "frail" if they fulfilled three or more criteria, "pre-frail" if they fulfilled one or two, and "robust" if none of the criteria was fulfilled. The metrics were slightly changed following the procedures used in similar studies with very old individuals (e.g., Gonzalez-Pichardo et al, 2013;Nyunt et al, 2017). In particular:…”
Section: Methodsmentioning
confidence: 99%
“…Literature suggests additional personal factors that might influence IADL performance in MCI [3], however with inconsistent findings. Age was found to be associated with impaired IADL performance in MCI [44,46], as well as depression [44,47], frailty [36], physical activity [48] and comorbidities [44,49]. In contrast, Mariani and colleagues revealed that IADL performance was more strongly related with cognitive function than physical comorbidities [33].…”
Section: Personal Factorsmentioning
confidence: 97%
“…Moreover, studies using clinical assessments of balance, e.g. POMA, revealed an association between IADL performance and balance in people with MCI [36].…”
Section: Physical Function Factorsmentioning
confidence: 99%